Design, synthesis and antibacterial properties of pyrimido[4, 5-b]indol-8-amine inhibitors of DNA gyrase. Issue 17 (15th September 2018) - McGarry, David H.; Cooper, Ian R.; Walker, Rolf; Warrilow, Catherine E.; Pichowicz, Mark; Ratcliffe, Andrew J.; Salisbury, Anne-Marie; Savage, Victoria J.; Moyo, Emmanuel; Maclean, John; Smith, Andrew; Charrier, Cédric; et al.
Graphical abstract: Highlights: Discovery of amide-linked pyrimido[4, 5- b ]indol-8-amine inhibitors of DNA gyrase. Potent against gram-positive bacteria (MIC < 1 µg/mL). Excellent activity against drug-resistant strains of Mycobacterium tuberculosis . Abstract: According to the World Health Organization (WHO), approximately 1.7 million deaths per year are caused by tuberculosis infections. Furthermore, it has been predicted that, by 2050, antibacterial resistance will be the cause of approximately 10 million deaths annually if the issue is not tackled. As a result, novel approaches to treating broad-spectrum bacterial infections are of vital importance. During the course of our wider efforts to discover unique methods of targeting multidrug-resistant (MDR) pathogens, we identified a novel series of amide-linked pyrimido[4, 5- b ]indol-8-amine inhibitors of bacterial type II topoisomerases. Compounds from the series were highly potent against gram-positive bacteria and mycobacteria, with excellent potency being retained against a panel of relevant Mycobacterium tuberculosis drug-resistant clinical isolates.